Differential Use of Image Enhancement Techniques by Experienced and Inexperienced Observers - Krupinski, Elizabeth A. (Springer-Verlag, 2005)
Full-field digital mammography (FFDM) systems are currently being used to acquire mammograms in digital format, but digital displays are less than ideal compared to traditional film-screen display. Certain physical properties of softcopy displays [e.g., modulation transfer function (MTF)] are less than optimal compared to film. We developed methods to compensate for some of these softcopy display deficiencies, based on careful physical characterization of the displays and image-processing software. A series of 100 FFDM and 60 digitized images was shown to six observers—half experienced (mammographers) and half inexperienced (radiology residents). The observers had to decide if a mass or microcalcification cluster was present and classify it as benign or malignant. A window could be activated that brought the image detail within the window to full resolution and corrected for the nonisotropic MTF of the Cathode Ray Tube (CRT) display. Experienced readers had better diagnostic performance and took less time to view the images. Experienced readers used window/level more than inexperienced readers, but inexperienced readers used magnification and the MTF compensation tool more often. Use of the magnification and the MTF tool increased reader decision confidence. Experienced and inexperienced readers use image-processing tools differently, with certain tools increasing reader confidence. Understanding how observers use image-processing tools may help in the development of better and more automated user interfaces.